2012
DOI: 10.7554/elife.00109
|View full text |Cite|
|
Sign up to set email alerts
|

Synaptic proteins promote calcium-triggered fast transition from point contact to full fusion

Abstract: The molecular underpinnings of synaptic vesicle fusion for fast neurotransmitter release are still unclear. Here, we used a single vesicle–vesicle system with reconstituted SNARE and synaptotagmin-1 proteoliposomes to decipher the temporal sequence of membrane states upon Ca2+-injection at 250–500 μM on a 100-ms timescale. Furthermore, detailed membrane morphologies were imaged with cryo-electron microscopy before and after Ca2+-injection. We discovered a heterogeneous network of immediate and delayed fusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
302
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(324 citation statements)
references
References 71 publications
16
302
1
Order By: Relevance
“…Though EPR data agreed with this model of membrane bridging (24), and increasing evidence supports the notion that the membrane-bridging activity of synaptotagmin-1 is critical for its function (7,(25)(26)(27)(28)(29)(30)(31), a recent study concluded that the bridging occurs by a fundamentally different mechanism that requires trans interactions between synaptotagmin-1 oligomers bound to each membrane, without binding of the bottom of the C 2 B domain to the lipids (29). This mechanism, which we refer to as the oligomerization model, is compared in Fig.…”
mentioning
confidence: 78%
“…Though EPR data agreed with this model of membrane bridging (24), and increasing evidence supports the notion that the membrane-bridging activity of synaptotagmin-1 is critical for its function (7,(25)(26)(27)(28)(29)(30)(31), a recent study concluded that the bridging occurs by a fundamentally different mechanism that requires trans interactions between synaptotagmin-1 oligomers bound to each membrane, without binding of the bottom of the C 2 B domain to the lipids (29). This mechanism, which we refer to as the oligomerization model, is compared in Fig.…”
mentioning
confidence: 78%
“…To study the molecular mechanisms of Cpx, several reconstituted systems have been developed (19,(39)(40)(41)(42). As we reported previously, the C-terminal domain is important for suppression of Ca 2+ -independent fusion in a single-vesicle content mixing assay with reconstituted full-length neuronal SNAREs, and synaptotagmin-1 (19,43,44).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Ca 2+ -solution was injected into the flow chamber consisting of 500 μM Ca 2+ , 500 nM Cy5 dye molecules (used as an indicator for the arrival of Ca 2+ in the evanescent field), and Cpx, Cpx fragments, or Cpx mutant at 2-μM concentration in buffer V. Ca 2+ -triggered fusion events were monitored within the same field-of-view upon injection for a 1-min period. The injection was performed at a speed of 66 μL/s by a motorized syringe pump (Harvard Apparatus) using a withdrawal method similar to the one described previously (19,39). All experiments were carried out at ambient temperature (25°C).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations